Suture and anchors may be retained during treatment of deep infection after rotator cuff repair: a systematic review. Issue 2 (13th February 2019) - Rosen, Michael R; Lakehomer, Harrison; Kasik, Connor S; Stephenson, Kyle
Abstract : Importance: Rotator cuff repairs (RCRs) are one of the most common orthopaedic surgeries performed, and infection is a rare but serious complication. It is important to know the ideal management of infection after RCR. Objective: To systematically review the literature regarding deep infection following RCR to characterise the success and failure rates of irrigation and debridement (I & D), with particular attention focused on potential predictors of failure, retention of suture anchor hardware and the necessity for serial I & Ds. Evidence review: Four databases (Embase, PubMed, Google Scholar and EBSCOHost) were screened for clinical studies involving the treatment of infection after RCR. A full-text review of eligible studies was conducted. Inclusion and exclusion criteria were applied to the searched studies. Data from the selected studies were combined for comparative analysis to elucidate factors associated with the success of I & D. Findings: We identified 11 eligible studies involving 172 patients. These studies described the number of I & D procedures necessary for successful treatment of infection after RCR. The mean number of I & Ds while retaining suture anchors and suture material was 2.3, compared with 2.2 I & Ds when removing all hardware. Propionibacterium acnes was the most common organism cultured, seen in 75 of 172 (43.6%) patients. Staphylococcus aureus and S. epidermidis accounted for 40 (23.3%) and 42 (24.4%) cases, respectively. Conclusions and relevance: In managing infection following RCR, the current literature supports retaining suture anchors and suture material when the prior repair is found intact at the initial I & D. Further studies are necessary to strengthen the evidence for retaining hardware and ensuring there is not a statistically significant difference between the number of I & Ds needed to eradicate infection with the routine retention versus removal of suture anchors in this setting. Level of evidence: Level IV, systematic review of Level III and IV studies.